Study of Sand Control Effects of. Nylon Net· Fences - Qu, Jlann Jun; Zhang, Ke Cun; Zu, Rui Ping; Lel, Jia Qiang; Fang, Hai Yan (Annals of Arid Zone, 2016)
Field monitoring and wind tunnel simulation of sand control effects of nylon net fences showed that these fences are not only more effective in sand-blocking, but also can divert the sand flow. Such function widens its application range and also provides an effective way to control movi?g sand in Gobi area. Nylon net fence, more effective than wooden fence, is of two types, namely dense type with an optimal porosity ranging from 40-50%. This type of fence can provide protection for downwind area up to 30 times the height of fence. Under medium wind velocity condition (V = 10-15 m.s-1), the sand-blocking rate can exceed 70%; even under very strong wind condition (V> 18 m.s-l) the sand accumulation rate can exceed 50%. Nylon net fence also deflects the moving sand, with a critical angle of 45°. If the angle between the fence and the prevailing wind direction exceeds 45° its sand diversion efficiency will be reduced.